Climatic insights on academic calendar shift in the Philippines - Villafuerte, II, Marcelino Q.; Juanillo, Edna L.; Hilario, Flaviana D. (2017)
A number of Philippine universities have shifted their academic calendar (AC) from JuneMarch (old AC) to August-May (new AC). Such AC shifting was primarily aimed to synchronize with other higher education institutions in Southeast Asia, which could provide flexibility for collaborative research works and eventually promote their global competitiveness. Considering the country?s climatic pattern, this study provides a comprehensive analysis on how the country?s climate could affect the recent AC shift. Subsequently, this study has revealed that school days seem to be better placed in the new AC than in the old AC, particularly in areas classified under rainy season Type 1, where rainy season occurs from mid-May to mid-October, and Type 3 (rainy season covers almost the latter half of the year). Such advantages of the new AC in comparison to the old AC include fewer rainy school days, lesser extreme rainfall events, and a reduced number of possible tropical cyclone-related cancellations of classes. However, a few downsides have been noted in implementing the new AC. It was revealed here that school days in the new AC, in areas characterized with rainy season Types 1 and 3, coincide with extremely hot days. Additionally, this study has revealed that graduation day seems to be better placed in the old AC than in the new AC because that day coincides with the rainy season and a higher possibility of tropical cyclone to occur in the latter, particularly over most areas in Luzon. These findings should therefore be considered in school-related activities to contribute in achieving a climate-resilient country. (Author's abstract)